New product development : Terra tumbler / Muhamad Nur Fahmi Mazalan ... [et al.] - Fahmi Mazalan, Muhamad Nur; Hamidun, Shahril; Shairan, Nur Artikah; Sulaiman, Shadiq Azim (2019)
Dehydration is one of the earliest symptoms of dehydration is one that is the most often overlooked: a headache. If ignored, the victim is subject to temperature related illnesses such as heat stroke and hypothermia. Dehydration can cause hikers to become confused and disoriented, which if hiking alone, can quickly lead an otherwise capable hiker to become lost. Dehydration victims often exhibit a lack of appetite from nausea and dizziness. The best way to prevent dehydration is to consciously drink water slowly over several hours before intense exercise. During periods of heavy exercise we should drink about one quart per hour. If our urine is clear and copious, then we know we are well hydrated.